POLLEN MORPHOLOGY AND ITS RELATIONSHIP TO THE TAXONOMY OF THE SOME TAXA OF HELICHRYSUM GAERTNER (ASTERACEAE) IN TURKEY - Elkiran, Omer; Bagci, Eyup; Evren, A. Harun (Pakistan Botanical Soc, 2017)
Palynological studies of Helichrysum chionophilum, Helichrysum noeanum, Helichrysum arenarium subsp. aucheri, Helichrysum graveolens, H. plicatum subsp. plicatum and H. plicatum subsp. polyphyllum (Asteraceae) from Turkey have been carried out. H. chionophilum, H. noeanum and H. arenarium subsp. aucheri are endemics to Turkey. Pollen features of both taxa were observed with the Light and Scanning Electron Microscopy (SEM). The pollen type of both taxa were determined as tricolporate, pollen shapes were spheroidal and oblate-spheroidal, reticular pollen ornamentation was observed. The studies show that the pollen of the six taxa are very similar regarding pollen shapes, apertures, and ornamentation, but may be distinguished by colpus length (Clg), pore width (Plt) and pore length (Plg). The findings obtained from the study are discussed with each other and the genus patterns.
Keywords: Helichrysum; Asteraceae; Pollen morphology; LM; SEM